Stability of Incineration bottom ash-amended marine clay with and without binders in water - Sun, Xinlei (2025)
Incineration bottom ash (IBA) is a by-product generated from incineration of municipal solid wastes, and it is mostly landfilled, especially for fine IBA. Reusing IBA with waste soils as filling materials in civil engineering can be a potential solution. However, the existing studies only focused on the air-cured IBA-soil mixtures in the laboratory, whereas in the field, the mixtures may contact water or immerse in water. Because IBA is rich in sulfates, the stability of IBA-soil mixtures in water may be compromised. Therefore, this study investigated the stability of IBA-marine clay (MC) mixtures in water. Ordinary portland cement (OPC) and granulated blast-furnace slag (GGBS) served as binders to stabilize/solidify IBA-MC. The appearance, strength, mineralogy, and microstructure of IBA-MC, OPC-IBA-MC, and GGBS-IBA-MC were studied. The results showed that all mixtures performed well when cured in air, but some deteriorated after soaking in water. IBA-MC and OPC-IBA-MC subjected to a short precuring period developed significant cracks and strength loss. Long precuring can reduce or eliminate the cracks on specimens during soaking, leading to higher strength. However, GGBS-IBA-MC had no surficial defects and only a slight strength decrease under both precuring periods. The mineralogy and microstructure of IBA-MC and stabilized IBA-MC revealed that the formation and growth of ettringite were responsible for the deterioration of IBA-MC and OPC-IBA-MC soaking in water.